Laparoscopically assisted cervical canalization and neovaginoplasty in a woman with cervical atresia and vaginal aplasia - Asami Kobayashi; Atsushi Fukui; Ayano Funamizu; Asami Ito; Rie Fukuhara; Hideki Mizunuma (Gynecology and Minimally Invasive Therapy, 2017)
Cervical atresia is a Müllerian duct system anomaly, and it is often associated with vaginal aplasia. We report the case of a 17-year-old girl who presented with primary amenorrhea and cyclical abdominal pain, and was diagnosed with cervical atresia and vaginal aplasia that were treated laparoscopically. Laparoscopically assisted cervical canalization and neovaginoplasty were performed to relieve dysmenorrhea and allow for sexual intercourse and fertility. We did not use a bowel segment, skin, or peritoneum as a graft for the neovaginoplasty. To prevent adhesions and promote epithelialization, we used an estrogen-containing cream. Moreover, we did not use a vaginal mold. The patient is free of cervical stenosis and able to have intercourse. Long-term follow-up is necessary to ensure a future pregnancy and childbirth.